Pengaruh Jam Kerja, Pendapatan dan Perlindungan Kerja terhadap Kesejahteraan Ojek Online: Studi pada Driver Grab di Kota Jambi - Salman Alparisy; Arsa Arsa; Agusriandi Agusriandi (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2025)
This research is titled "The Influence of Working Hours, Income, and Job Protection on the Welfare of Online Motorcycle Taxi Drivers (A Study on Grab Drivers in Jambi City)." The objectives of this study are: 1) To explain the effect of working hours on the welfare of Grab drivers in Jambi City. 2) To explain the effect of income on the welfare of Grab drivers in Jambi City. 3) To explain the effect of job protection on the welfare of Grab drivers in Jambi City. 4) To explain the combined effect of working hours, income, and job protection on the welfare of Grab drivers in Jambi City. The research method used by the researcher is a quantitative approach. The results of this study are: 1) From the regression test, it was found that working hours do not have a significant effect on the welfare of Grab drivers in Jambi City. 2) From the regression test, it was found that income significantly affects the welfare of Grab drivers in Jambi City. 3) From the regression test, it was found that job protection significantly affects the welfare of Grab drivers in Jambi City. 4) Simultaneously, working hours, income, and job protection significantly affect the welfare of Grab drivers in Jambi City.